Dynamic and Assembly of Epiphyte and Endophyte Lactic Acid Bacteria During the Life Cycle of Origanum vulgare L. - Pontonio, Erica; Di Cagno, Raffaella; Tarraf, Waed; Filannino, Pasquale; De Mastro, Giuseppe; Gobbetti, Marco (Frontiers in Microbiology, 2018)
Origanum vulgare L. (oregano) was chosen as suitable model to investigate the ability of the endophyte-microbiome, especially that of lactic acid bacteria, to develop specific interactions with the plant, mediated by the essential oils (EOs). Combined culture-dependent and -independent approaches analyzed the bacterial dynamic and assembly of Origanum vulgare L. throughout the life cycle. Epiphyte bacteria were more abundant than the endophyte ones. The number of presumptive lactic acid bacteria increased throughout oregano life cycle, according to the plant organ. Diverse species of lactic acid bacteria populated the plant, but Lactobacillus plantarum stably dominated both epiphyte and endophyte populations. High-throughput DNA sequencing showed highest epiphyte bacterial diversity at early-vegetative and full-flowering stages, with blooming signing the main microbial differentiation among plant organs. Proteobacteria, Actinobacteria and Bacteroidetes, and Firmicutes and Cianobacteria at lower abundance were the main phyla. Various genera were detectable, but oregano harbored mainly Methylobacterium, Sphingomonas, Rhizobium and Aurantimonas throughout phenological stages. Firmicutes epiphyte and endophyte microbiotas were different, with a core microbiota consisting of Bacillus, Exiguobacterium, Streprococcus, Staphylococcus and Lactobacillus genera. Bacillus dominated throughout phenological stages. High-throughput DNA sequencing confirmed the dominance of L. plantarum within the epiphyte and endophyte populations of lactic acid bacteria. Yields of EOs varied among plant organs and throughout plant life cycle. L. plantarum strains were the most resistant to the total EOs (mainly thymol and carvacrol) as extracted from the plant. The positive correlation among endophyte lactic acid bacteria and the EOs content seems confirm the hypothesis that the colonization within plant niches may be regulated by mechanisms linked to the synthesis of the secondary metabolites.